2001
DOI: 10.1248/jhs.47.278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Mode of Action of Chlorinated Ethylenes on the Expression of Rat CYP Forms.

Abstract: Many environmental chemicals (xenobiotics), including polychlorinated ethylenes (CEs), are known to be metabolically intoxicated via the formation of hazardous intermediates (referred to as biological activation), while the expression of metabolic enzymes might be interfered with by xenobiotics at various stages in a system to minimize their adverse biological effects on the host animals. Three CEs, i.e., tetrachloroethylene (PCE), trichloroethylene (TCE) and 1,1-dichloroethylene (1,1-DCE), were comparatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…11) In the present study, the PB-dependent potentiation of hepatic 2α-TSH activity was confirmed to be completely reversed to the basal level when the rats were treated with 1,1-DCE, although the details of the mechanisms controlling these findings remain to be elucidated. …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…11) In the present study, the PB-dependent potentiation of hepatic 2α-TSH activity was confirmed to be completely reversed to the basal level when the rats were treated with 1,1-DCE, although the details of the mechanisms controlling these findings remain to be elucidated. …”
Section: Discussionsupporting
confidence: 59%
“…10) On the contrary, chlorinated ethylenes (CEs) have been studied extensively for their effects on the expression of CYP1A, 2B, and 2E1 in animal models. 5,[11][12] Although CYP2C is reportedly one of the major P450 forms by which CEs are metabolized, 13) the effects of CEs on the expression of CYP2C have not been studied extensively. Therefore the present study focuses on the in vivo effects of CEs including TCE and PCE, both under stringent legislative control as environmental pollutants, on the expression of CYP2C in rat liver and lung.…”
Section: )mentioning
confidence: 99%
“…5) In rat hepatocyte primary culture, CEs including 1,1-DCE were apt to work as inducers of CYP forms (Nakahama et al, unpublished). Therefore, the suppressive effects of CEs, particularly 1,1-DCE, observed in the whole animals were not really considered to be direct effects.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane was hybridized separately with either a CYP2B, CYP2E1 or G3PDH cDNA probe as described previously. 5) The membrane was exposed to an Imaging Plate and analyzed by Storm TM830. Statistics ---Statistical significance was determined using a Student's t-test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation